FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS RASA DALAM TARI JAWA GAYA SURAKARTA - Katarina Indah Sulastuti (Institut Seni Indonesia Surakarta, 2013)
This article discusses the factors that affect the quality of taste/ rasa In Surakarta Style Javadance. The quality of the taste in dance has subjective nature that arise a various interpretation ofeach individual. The differences that appear to be an obstacle in communication. The discussionis analyzed using the communication psychology theory, especially symbolic communication.The result of discussion is explained by several factors namely: emotional mood, cognitive scheme,atmosphere exposure, individual predisposition, and the level of character/ theme identification. Inthe following discussion also raise the essential elements as the determinants of quality of taste orrasa in Surakarta style Java Dance, which consist material and immaterial elements.